Acquired resistance to trastuzumab/pertuzumab or to T‐DM1 in vivo can be overcome by HER2 kinase inhibition with TAS0728. Issue 6 (30th April 2020) - Irie, Hiroki; Kawabata, Rumi; Fujioka, Yayoi; Nakagawa, Fumio; Itadani, Hiraku; Nagase, Hideki; Ito, Kimihiro; Uchida, Junji; Ohkubo, Shuichi; Matsuo, Kenichi
Abstract: HER2‐targeting antibodies (trastuzumab, pertuzumab) and a HER2‐directed antibody‐drug conjugate (trastuzumab emtansine: T‐DM1) are used for the treatment of HER2‐overexpressing breast cancer. However, these treatments eventually become ineffective due to acquired resistance and there is an urgent need for alternative therapies. TAS0728 is a small‐molecule, irreversible selective HER2 kinase inhibitor. In the present study, we established new in vivo models of cancer resistance by continuous exposure to a combination of trastuzumab and pertuzumab or to T‐DM1 for evaluating the effect of TAS0728 on HER2 antibody‐resistant populations. Treatment with trastuzumab and pertuzumab or with T‐DM1 initially induced tumor regression in NCI‐N87 xenografts. However, tumor regrowth during treatment indicated loss of drug effectiveness. In tumors with acquired resistance to trastuzumab and pertuzumab or to T‐DM1, HER2‐HER3 phosphorylation was retained. Switching to TAS0728 resulted in a significant anti‐tumor effect associated with HER2‐HER3 signal inhibition. No alternative receptor tyrosine kinase activation was observed in these resistant tumors. Furthermore, in a patient‐derived xenograft model derived from breast cancer refractory to both trastuzumab/pertuzumab and T‐DM1, TAS0728 exerted a potent anti‐tumor effect. These results suggest that tumors with acquired resistance to trastuzumab and pertuzumab and to T‐DM1 are still dependent on oncogenic HER2‐HER3 signaling and are vulnerable to HER2 signal inhibition by TAS0728. These results provide a rationale for TAS0728 therapy for breast cancers that are refractory to established anti‐HER2 therapies. Abstract : We successfully established, for the first time, in vivo tumor models of trastuzumab and pertuzumab or T‐DM1 resistance, and TAS0728 monotherapy was effective against tumors resistant to these therapies. These results imply that the tumors that are resistant to trastuzumab and pertuzumab or to T‐DM1 do not show cross‐resistance to TAS0728, and that acquired resistance to these therapies can be overcome by HER2 kinase inhibition with TAS0728 in vivo. TAS0728 is a potentially useful treatment option for patients with tumors refractory to established anti‐HER2 antibodies and HER2‐targeting ADCs.